41.5k views
4 votes
Expand and simplify (x + 5)(x + 5)

User Starturtle
by
5.3k points

2 Answers

3 votes

the answer i believe is

x^2+10x+25

User FarhadA
by
6.0k points
6 votes

Method 1:

Use distributive property: (a + b)(c + d) = ac + ad + bc + bd

(x + 5)(x + 5) = (x)(x) + (x)(5) + (5)(x) + (5)(5) = x² + 5x + 5x + 25

= x² + 10x + 25


Method 2:

a · a = a², therefore (x + 5)(x + 5) = (x + 5)².

Use (a + b)² = a² + 2ab + b².

(x + 5)² = x² + 2(x)(5) + 5² = x² + 10x + 25

User Rajib Kumar De
by
6.2k points